Proyecto de emprendimiento empresarial de exportación de artesanías textiles otavaleñas de alta calidad orientadas al mercado de Nueva York - Aumala Villegas, Elvira Betsabé (2015)
Within this entrepreneurial project aimed to the export of ponchos and hammocks we studied the market of New York city where our product would be offered, for which we determined the objectives of this project in relation to the likelihood of problems within the local market where we would be provided of the product itself, which is located in Otavalo, within the province of Imbabura in our country. The methodology and frame of the work indicates the kind of research that took place and the tools used to determine the sample. These same tools helped us to conduct polls in order to determine tastes and preferences of the potential clients. Each product to be exported is studied with the collected information which was useful to identify the objective market. We developed the technical specifications to establish the size of our project according to the necessary resources for its own implementation. The viability of the project can be seen in the financial study concluding that the proposal is financially able to be started within the organizational analysis of the company that will be created for the purpose mentioned before.